Experiment with magnets - Taylor-Butler, Christine (Ann Arbor, Mich. : Cherry Lake Pub., 2011)
Offers an overview of the scientific method and provides instructions for three experiments which teach about magnets.
Let's experiment! -- Experiment #1: Let the force be with you! -- Experiment #2: Do opposites really attract? -- Experiment #3: Share the power -- Do it yourself!
Includes bibliographical references (p. 31) and index.
4.0
3-6
3-6
Keywords: Magnetism -- Experiments -- Juvenile literature; Science projects -- Juvenile literature; Magnetism -- Experiments; Science projects; Magnetism -- Experiments; Science projects